Tekst biblijny i sprawy „zbyt powszednie”? Na marginesie kwestii tabu językowego w tradycji czeskiego przekładu biblijnego - Bartoň, Josef (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The case study deals with the fortunes of translation equivalents of the words ἀφεδρών//secessus (in Matthew 15,17 and Mark 7,19) and γυμνός//nudus (in John 21,7) in the Czech Biblical tradition. The paper presents the material from almost fifty Czech translations (from the end of the 13th century to this day) and shows that the expressions (notions) draught, toilet and naked disappear in certain moments and are missing in most of the translations. The author tries to demonstrate in his analyses and interpretations when, under which circumstances and why there was this specific secondary tabooization that itself (slightly) disturbs the taboo of the inviolability of the content of the sacred text.